Problem 476

Tommy has some money at home from his graduation modeled by the function h(x) = 350. He read about a bank that has savings accounts that accrue interest according to the function s(x) = (1.04)x − 1. Tommy is thinking about putting his money into the savings account to gain interest. Using complete sentences, explain to Tommy how he can combine his functions to create a new function, and explain what this new function means.

h(x) = 350
s(x) = (1.04)^{(x-1)} , here x is the money deposited

we can combine these two function by putting h(x) as x in the function s(x) as h(x) is the money he had.
new function

f(x) = (1.04)^{(h(x)-1)}

f(x) = (1.04)^{(350-1) }

f(x) = (1.04)^{(349)}

f(x) = 880309.55

this function shows that he will get 880309.55 money as the interest of initial money he had.



One thought on “Problem 476

  1. This is incorrect. It should be h(x) * s(x) = 350(1.04)^(x − 1)
    and this function is the balance after x years in the savings account.

Leave a Reply

Your email address will not be published. Required fields are marked *